I need help solving this. Please show all steps. Thanks!
Simplify x^2(1-2x^3)^-1/2(-3x^2) + (1-2x^3)^1/2(2x)
$\displaystyle \frac{-3x^4}{(1-2x^3)^{\frac{1}{2}}}+\frac{2x(1-2x^3)^{\frac{1}{2}}}{1}=\frac{-3x^4+2x(1-2x^3)}{(1-2x^3)^{\frac{1}{2}}}=$
$\displaystyle \frac{-3x^4+2x-4x^4}{(1-2x^3)^{\frac{1}{2}}}=\frac{-7x^4+2x}{(1-2x^3)^{\frac{1}{2}}}=$
Can you see where this thing is going? Maybe you can factor an x out of the numerator, but I don't see much more simplification here. Maybe you could try rationalizing the denominator.